Maturity Level and Competence of Village Apparatus in Readiness to Implement Digital Accounting Information Systems - Winda Virginia; Resfika Aswira; Risna Risna (Agregat: Jurnal Ekonomi dan Bisnis, 2025)
This study investigates the relationship between the maturity level of village fund management and the competence of village officials in determining the readiness to implement a Digital Accounting Information System (SIAD). Unlike previous studies that separately analyzed either organizational maturity or human resource competence, this research integrates both constructs into a single explanatory framework, highlighting their direct and indirect effects through community trust as a mediating variable. Using an quantitative design, data were collected through questionnaires distributed to 111 village officials in Buton Regency, Southeast Sulawesi. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS). The findings reveal that the maturity level of village fund management has a significant effect on SIAD implementation readiness, both directly and indirectly through community trust. Conversely, the competence of village officials does not directly affect readiness but significantly contributes to strengthening public trust. These results indicate that the readiness of village governments to adopt SIAD is primarily determined by the maturity of governance structures, which must be supported by human resource capacity building and reinforced by public trust. The study contributes to the growing body of literature on digital governance by proposing an integrated empirical model for assessing digital accounting system readiness at the village level in developing countries